Jan Ludwik Popławski’s fascination with the Polish ‘Common People’ - Kowalczyk, Michał (Saeculum Christianum. Pismo Historyczne, 2021)
Jan Ludwik Popławski (1854-1908) was one of the fathers of the Polish National Democratic ideology in the late 19th and early 20th century. He was particularly fascinated with matters pertaining to the common people, and especially Polish peasantry. He considered them to be the genuine Poles, free of foreign influences. It is worth pointing out that that he also served as an inspiration to Roman Dmowski, the founder of the National Democracy movement and one of the leaders whose efforts secured Polish independence. According to Popławski, the Polish gentry were servile to the powers occupying Poland. He therefore hoped that the common people would play a greater role in the political life of the nation.